2022
DOI: 10.1002/1873-3468.14435
|View full text |Cite
|
Sign up to set email alerts
|

Neurospora casein kinase 1a recruits the circadian clock protein FRQvia the C‐terminal lobe of its kinase domain

Abstract: Timing by the circadian clock of Neurospora is associated with hyperphosphorylation of frequency (FRQ), which depends on anchoring casein kinase 1a (CK1a) to FRQ. It is not known how CK1a is anchored so that approximately 100 sites in FRQ can be targeted. Here, we identified two regions in CK1a, p1 and p2, that are required for anchoring to FRQ. Mutation of p1 or p2 impairs progressive hyperphosphorylation of FRQ. A p1‐mutated strain is viable but its circadian clock is non‐functional, whereas a p2‐mutated str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…2020; Marzoll et al . 2022b, 2022a), which is consistent with a large number of phosphorylatable residues identified on it. Although over 100 phosphosites have been identified (Baker et al .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…2020; Marzoll et al . 2022b, 2022a), which is consistent with a large number of phosphorylatable residues identified on it. Although over 100 phosphosites have been identified (Baker et al .…”
Section: Discussionsupporting
confidence: 82%
“…FRQ has been predicted to be a largely unstructured protein comprising many disordered regions that make most of its residues exposed and accessible by kinases in the cell (Hurley et al 2013;reviewed in Pelham et al 2020;Marzoll et al 2022bMarzoll et al , 2022a, which is consistent with a large number of phosphorylatable residues identified on it.…”
Section: Discussionmentioning
confidence: 87%
“…FRQ has been predicted to be a largely unstructured protein comprising many disordered regions that make most of its residues exposed and accessible by kinases in the cell ( Hurley et al 2013 ; reviewed in Pelham et al 2020 ; Marzoll et al 2022b , 2022a ), which is consistent with a large number of phosphorylatable residues identified on it. Although over 100 phosphosites on FRQ have been unambiguously documented ( Baker et al 2009 ; Tang et al 2009 ) and partially confirmed by a recent publication ( Horta et al 2019 ), and Ala mutations to some of these phosphoresidues have been shown to alter period lengths, their functions are still largely unknown due to lack of systematic mutagenesis analyses to all of them.…”
Section: Discussionmentioning
confidence: 82%
“…For instance, CK1 in fungi and animals and CK2 in plants are crucial for the phosphorylation of circadian clock proteins. In eukaryotes, the ubiquitin–proteasome system and autophagy are involved in the modification and degradation of clock proteins [ 47 , 48 ].…”
Section: The Molecular Network Of the Circadian Clockmentioning
confidence: 99%